Yield and Yield Components of Red Onion (Allium ascalonicum L.) Influenced by Application of Amino Acid Fertilizer And Triacontanol - Putra, Anggara Ista; Waluyo, Budi; Nihayati, Ellis (Research Journal of Life Science, 2022)
Red onions are one of the agricultural products with a relatively high demand for the consumer market in Indonesia, but the productivity figure is quite low when compared to other countries (FAO, 2021). This study seeks to explore the effectiveness of the application of amino acid fertilizer and triacontanol in increasing the yield and yield components of red onions. The study took place in Karangploso District, Malang from April to August 2021. Employing a randomized block design, this study used 2 factors, which are amino acid fertilizers (A1: 1000 ppm; A2: 3000 ppm; A3: 5000 ppm) and triacontanol (T0: 0 ppm; T1: 5ppm; T2: 10 ppm). Each combination is repeated 3 times. As a results, amino acid fertilizers can significantly affect the number of red onions bulbs, yields per hectare, economic weight, and economic weight loss. A significant result was seen in the application of triacontanol on red onions yields per hectare and economic weight. The interaction of characters of bulb length was shown in the combination of 5-10 ppm triacontanol with amino acid fertilizer. The best response, which ranged from 10.64% to 11.67%, was noted in fertilizer with 5000 ppm of an amino acid fertilizer. As the concentration of amino acid fertilizer in combination with triacontanol increased, the total bulb fresh weight increased as well, in which, 5000 ppm of amino acid fertilizer could increase the weight by 45,23-45,43 g clump-1, which was greater than the response of the 1000 ppm amino acid fertilizer combination.